2009
DOI: 10.1007/s00128-009-9807-4
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic Sources of Heavy Metals in the Indian Ocean Coast of Kenya

Abstract: Water and surface sediment samples from Rivers Sabaki, Ramisi and Vevesi that flow into the Indian Ocean coast of Kenya were analysed for heavy metals. The sediment concentrations of exchangeable cations (in microg/g) for Co, Cu, Mn, Ni, Pb, Sn and Zn ranged from 0.10 to 506.75 (for Mn at Sabaki), constituting between 2% and 20% of the total metal concentrations obtained by digestion with strong acid. Cu, Mn, Ni, Pb and Zn were more leachable with 0.1 N HCl. The total dissolved metal in water and the total sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
4
12
0
Order By: Relevance
“…Hydrographic data illustrated the actual data range for marine environment with high temperature, seawater range of salinity and slightly alkaline condition [2] and [25] for temperature and pH. However, DO in this study was found to be the highest compared to both studies.…”
Section: Heavy Metal Distributionssupporting
confidence: 60%
See 4 more Smart Citations
“…Hydrographic data illustrated the actual data range for marine environment with high temperature, seawater range of salinity and slightly alkaline condition [2] and [25] for temperature and pH. However, DO in this study was found to be the highest compared to both studies.…”
Section: Heavy Metal Distributionssupporting
confidence: 60%
“…However, DO in this study was found to be the highest compared to both studies. Water quality parameters could change the bioavailability of metals in the pore waters and the release rate of metals from sediments [7], thus can modify heavy metals chemistry and toxicity on aquatic life [2]. For example, the study [25] found that metals especially Pb experienced flocculation better at lower salinity level and thus reduced its concentration in the environment due to changing of the metal to the particulate phase.…”
Section: Heavy Metal Distributionsmentioning
confidence: 99%
See 3 more Smart Citations